Performance of road-traffic-based exposure proxies against personal PM2.5 measurements in three Sub-Saharan African countries - Handsome Bongani Nyoni; Terence Darlington Mushore; Laura Munthali; Sibusisiwe Audrey Makhanya; Laurine Chikoko; Stanley Luchters; Matthew F Chersich; Fortunate Machingura; Liberty Makacha; Benjamin Barratt; Hiten D Mistry; Marie Laure Volvert; et al. (Air Quality, Atmosphere & Health, 2026)

The Impact of Ambient Heat on Perinatal and Neonatal Health in the Context of Climate Change: A Scoping Review - Eline Holvoet; Paul Lokubal; Matthew Chersich; Veronique Filippi; Debra Jackson; Darshnika Lakhoo; Shobna Sawry; Shuchita Gupta; Stanley Luchters (Current Environmental Health Reports, 2026)

Trimester-specific exposure to multiple heat indicators and adverse birth outcomes across four European countries - Mian Bao; Federica Nobile; Michalis Koureas; Isabella Bottini; Elizaveta Fomenko; Chloe Brimicombe; Veronika Tirado; Varvara Mouchtouri; Christos Hadjichristodoulou; Petter Ljungman; Matthew Chersich; Debra Jackson; et al. (Environmental Research, 2026)

Publisher Correction to: Quantifying intra-urban socio-economic and environmental vulnerability to extreme heat events in Johannesburg, South Africa - Craig Parker; Craig Mahlasi; Tamara Govindasamy; Lebohang Radebe; Nicholas Brian Brink; Christopher Jack; Madina Doumbia; Etienne Kouakou; Matthew Chersich; Guéladio Cissé; Sibusisiwe Makhanya; Aakin Bobola; et al. (International Journal of Biometeorology, 2025)

Quantifying intra-urban socio-economic and environmental vulnerability to extreme heat events in Johannesburg, South Africa - Craig Parker; Craig Mahlasi; Tamara Govindasamy; Lebohang Radebe; Nicholas Brian Brink; Christopher Jack; Madina Doumbia; Etienne Kouakou; Matthew Chersich; Guéladio Cissé; Sibusisiwe Makhanya; Aakin Bobola; et al. (International Journal of Biometeorology, 2025)
Urban populations face increasing vulnerability to extreme heat events, particularly in rapidly urbanising Global South cities where environmental exposure intersects with socioeconomic inequality and limited healthcare access. This study quantifies heat vulnerability across Johannesburg, South Africa, by integrating high-resolution environmental data with socio-economic and health metrics across 135 urban wards. We examine how historical urban development patterns influence contemporary vulnerability distributions using principal component analysis and spatial statistics. Environmental indicators (Land Surface Temperature (LST), vegetation indices, and thermal field variance) were combined with socioeconomic and health variables (including indicators on crowded dwellings and healthcare access, self-reporting of chronic diseases) in a comprehensive vulnerability assessment. Principal Component Analysis revealed three primary dimensions explaining 56.6% (95% CI: 52.4–60.8%) of the total variance: urban heat exposure (31.5%), health status (12.8%), and socio-economic conditions (12.3%). Built-up areas showed weak but significant correlations with heat indices (ρ = 0.28, p < 0.01), while higher poverty levels demonstrated moderate positive correlations with LST (ρ = 0.41, p < 0.001). The spatial analysis identified significant clustering of vulnerability (Global Moran's I = 0.42, p < 0.001), with distinct high-vulnerability clusters in historically disadvantaged areas. Alexandra Township showed the highest vulnerability(HVI score: 0.87, LST: 29.8 °C ± 0.4 °C, NDVI: 0.08 ± 0.02), with factors characterising the high vulnerability in that area including limited healthcare access and extreme heat exposure. Northern suburbs formed a significant low-vulnerability cluster (Mean HVI = 0.23 ± 0.07, p < 0.001), benefiting from greater vegetation coverage and better healthcare access. These findings demonstrate how historical planning decisions continue to shape contemporary environmental health risks, with vulnerability concentrated in areas of limited healthcare access and high extreme heat exposure. Results suggest the need for targeted interventions that address both environmental and social dimensions of heat vulnerability, particularly focusing on expanding healthcare access in identified hotspots and implementing community-scale green infrastructure in high-risk areas. This study provides an evidence-based framework for prioritising heat-resilience initiatives in rapidly urbanising Global South cities while highlighting the importance of addressing historical inequities in urban adaptation planning.

Association between ambient air pollution a week prior to delivery and preterm birth using a nationwide study in Sweden - Nabeel Aziz; Massimo Stafoggia; Olof Stephansson; Nathalie Roos; Sari Kovats; Matthew Chersich; Veronique Filippi; Cherie Part; Britt Nakstad; Shakoor Hajat; Petter Ljungman; Jeroen de Bont (International Journal of Hygiene and Environmental Health, 2024)

Physiological mechanisms of the impact of heat during pregnancy and the clinical implications: review of the evidence from an expert group meeting - Louisa Samuels; Britt Nakstad; Nathalie Roos; Ana Bonell; Matthew Chersich; George Havenith; Stanley Luchters; Louise-Tina Day; Jane E. Hirst; Tanya Singh; Kirsty Elliott-Sale; Robyn Hetem; et al. (International Journal of Biometeorology, 2022)
Many populations experience high seasonal temperatures. Pregnant women are considered vulnerable to extreme heat because ambient heat exposure has been linked to pregnancy complications including preterm birth and low birthweight. The physiological mechanisms that underpin these associations are poorly understood. We reviewed the existing research evidence to clarify the mechanisms that lead to adverse pregnancy outcomes in order to inform public health actions. A multi-disciplinary expert group met to review the existing evidence base and formulate a consensus regarding the physiological mechanisms that mediate the effect of high ambient temperature on pregnancy. A literature search was conducted in advance of the meeting to identify existing hypotheses and develop a series of questions and themes for discussion. Numerous hypotheses have been generated based on animal models and limited observational studies. There is growing evidence that pregnant women are able to appropriately thermoregulate; however, when exposed to extreme heat, there are a number of processes that may occur which could harm the mother or fetus including a reduction in placental blood flow, dehydration, and an inflammatory response that may trigger preterm birth. There is a lack of substantial evidence regarding the processes that cause heat exposure to harm pregnant women. Research is urgently needed to identify what causes the adverse outcomes in pregnancy related to high ambient temperatures so that the impact of climate change on pregnant women can be mitigated.